Public Financial Management and Its Impact On Egyptian National Railway - Shabana, Dalia (International Journal of Economics and Financial Issues, 2018)
The study focuses on improving the quality of public financial management (PFM) over governmental entities to attain public welfare. Thus, local authorities, which are public bodies deal with numerous products and services offered to society at social prices, face deficiencies such as accumulated losses and low employees productivity. In Egypt, local authorities are known as Economic Authorities (EA)s. As an example, Egyptian National Railway (ENR) is the sole economic authority responsible for rail network, yet it undergoes deteriorating financial position over decades. Keywords: Public Financial Management, Economic Authorities, Egyptian National Railway Authority JEL Classifications: E62, H54, P43, O23, G18, M48